Avaliações bioquímicas séricas e hepáticas do extrato de yacon (Polymnia sonchifolia) Poepp. & Endl. - Fernandes, A. A H [UNESP]; Bordon, J. G. [UNESP]; Batistella, R. F. [UNESP]; Nascimento, S. M. [UNESP]; Silva, M. S. [UNESP]; Alves, M. J Q F [UNESP] (My University, 2002)
Yacon is a medicinal plant, the tuberous roots of which have been thought to contain a large amount of fructan (oligosaccharides). Purpose - The aim of paper was to study the effect of aqueous extracts of yacon on biochemical parameters of clinical importance in rats. The animals (male, wistar, weighing approximately 300g) were divided in 3 groups: G1(n=8)= water control; G2(n=8)= aqueous extract of roots (0,17g/100g/day); G3(n=8)= aqueous extract of leaves (25mg/100g/day). The serum samples were obtained after 30 days, and the biochemical parameters were measured. The livers were removed and homogenized in 0,01M phosphate buffer pH 7,0 and then the supernatant fractions were used for enzyme assay. Significantly increased serum glucose was observed in G2 (206,72±91,27 mg/dL). The groups G2 and G3 rats had higher (p<0,05) urea concentration, while creatinin level decreased (p<0,05). The serum albumin concentration showed a tendency to remain in G2 (2,44±0,45 g/dL) and G3 (2,84±0,50 g/dL). Aqueous extracts administration markedly decreased (p<0,05) the activities of ALT in the liver and greatly increased these enzymatic activities in blood. The serum alkaline phosphatase activity increased (p<0,05) in rats receiving the aqueous extract of root (192,75±20,95 U/dL), while aqueous extract of leaves reduced it (129,57±19,93 U/dL). The results indicated that the extract of yacon promoted changes of the biochemical parameters.
Serum and hepatic biochemical evaluations of yacon (Polymnia sonchifolia) extract
Keywords: Asteraceae; Fructans; Liver; Medicinal plants; Metabolism; Serum protein; Therapies alternatives; alkaline phosphatase; fructan; oligosaccharide; plant extract; polymnia sonchifolia extract; unclassified drug; animal cell; aqueous solution; biochemical composition; blood sampling; enzyme activity; enzyme assay; liver parenchyma; medicinal plant; nonhuman; plant leaf; plant root; rat